Leadership Levels and Personality Traits of Female Managers in Select Industries in the Philippines - Barcelona, Alvin B; Gopez, Diana Ruby S; Mariano, Trisha Ann S; Pedreña, Julio Jose M; Santiago, Jeanne Lou M (International Journal of Economics, Business and Management Studies, 2022)
There is a paucity of empirical knowledge and a lack of descriptive portrait about women leadership and their managerial characteristics. The present study attempted to address the literature gap by investigating the correlation between the leadership levels and personality traits of female managers in Metro Manila, Philippines. This non-experimental research involved 100 female managers in the fields of banking, hospitality, and education using purposive sampling technique. The instruments used in this study were Maxwell’s Five Leadership Levels and Goldberg’s Big-five inventory scale. The findings of this study reveal that 31% of the respondents are in Level 1 and 27% are in Level 5. Also, female managers generally have a high level of openness, conscientiousness, and agreeableness and a moderate level of extroversion and neuroticism. Moreover, the five leadership levels are associated with two out of five personality traits: extroversion (X2=19.7,p=0.011) and neuroticism (X2=11.1,p=0.018). Further tests show that there are no significant differences in the leadership levels in terms of the demographic information of the respondents. These results depict that female managers think in abstract and complex ways, are highly organized and determined, have an inclination to make interaction with their team members, experience a great deal of empathy, tend to get pleasure from serving and taking care of their team members, and are relatively prone to negative emotions.